Adolescents in Drug Abuse in Sumbawa Regency: A Legal Sociological Review of Weak Social Control and Legal Awareness - Siswadi, Imran (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Drug abuse among adolescents in Sumbawa Regency has shown a significant increase in recent years, with a growing number of rehabilitated users coming from the 13–18 age group. This phenomenon is not merely a legal violation but also a social symptom arising from weakened social control and low legal awareness. This study aims to analyze the social factors that contribute to adolescents’ vulnerability to drug abuse, focusing on the roles of family, school, peer environment, and the local legal culture. Using qualitative content analysis of online news, institutional reports, and local media publications, this research integrates three major theoretical frameworks: social control theory, differential association theory, and concept of legal consciousness. The findings indicate that the weakening of adolescents’ social bonds with family and school is a key factor that creates space for deviant behavior. Interactions within peer networks serve as a medium for learning and normalizing drug use. Furthermore, low legal awareness leads adolescents to underestimate the legal and moral consequences of their actions, rendering formal law ineffective as a mechanism of social control. Study concludes that drug abuse among adolescents in Sumbawa is socio-cultural problem that requires a multidimensional response, including strengthening family and school-based social control.